Answer:
11
Step-by-step explanation:
5(2+4)-(2+3^3)
=5(8)-(2+27)
=40-29
=11
To find G of F first solve f(x) by replacing x with -7
F(x) = x^2 +6
= -7^2 +6
= 49 +6 = 55
So f(x) = 55
Now replace the X in the g(x) equation with 55
g(x) = x+8 / x
= 55+8 / 55
= 63/55
The last choice is the correct answer.
Answer:
-54
Step-by-step explanation:
Answer:
2x + 3y = 6
Step-by-step explanation:
obtain the equation in slope- intercept form
y = mx + c ( m is the slope and c the y-intercept )
here m = -
and c = 2
y = -
x + 2 ← in slope-intercept form
multiply all terms by 3 to eliminate the fraction
3y = - 2x + 6 ( add 2x to both sides )
2x + 3y = 6 ← in standard form